Isolation and characterization of lactic acid bacteria with potential probiotic activity and further investigation of their activity by α-amylase and α-glucosidase inhibitions of fermented batters - Huligere, Sujay S.; Chandana Kumari, V. B.; Alqadi, Taha; Kumar, Saurabh; Cull, Charley A.; Amachawadi, Raghavendra G.; Ramu, Ramith (Frontiers in Microbiology, 2023)
Probiotic microbiota plays a vital role in gastrointestinal health and possesses other beneficial attributes such as antimicrobial and antibiotic agents along with a significant role in the management of diabetes. The present study identifies the probiotic potential of Lactobacillus spp. isolated from three traditionally fermented foods namely, jalebi, medhu vada, and kallappam batters at biochemical, physiological, and molecular levels. By 16S rRNA gene amplification and sequencing, the isolates were identified. A similarity of >98% to Lacticaseibacillus rhamnosus RAMULAB13, Lactiplantibacillus plantarum RAMULAB14, Lactiplantibacillus pentosus RAMULAB15, Lacticaseibacillus paracasei RAMULAB16, Lacticaseibacillus casei RAMULAB17, Lacticaseibacillus casei RAMULAB20, and Lacticaseibacillus paracasei RAMULAB21 was suggested when searched for homology using NCBI database. Utilizing the cell-free supernatant (CS), intact cells (IC), and cell-free extract (CE) of the isolates, inhibitory potential activity against the carbohydrate hydrolyzing enzymes α-glucosidase and α-amylase was assessed. CS, CE, and IC of the isolates had a varying capability of inhibition against α-glucosidase (15.08 to 59.55%) and α-amylase (18.79 to 63.42%) enzymes. To assess the probiotic potential of seven isolates, various preliminary characteristics were examined. All the isolates exhibited substantial tolerance toward gastrointestinal conditions and also demonstrated the highest survival rate (> 99%), hydrophobicity (> 65%), aggregation (> 76%), adherence to HT-29 cells (> 84%), and chicken crop epithelial cells suggesting that the isolates had a high probiotic attribute. Additionally, the strains showed remarkable results in safety assessment assays (DNase and hemolytic), and antibacterial and antibiotic evaluations. The study concludes that the lactic acid bacteria (LAB) characterized possesses outstanding probiotic properties and has antidiabetic effects. In order to obtain various health advantages, LAB can be utilized as probiotic supplements.